Porous polymer microneedles with interconnecting microchannels for rapid fluid transport. Issue 54 (17th May 2016) - Liu, Liming; Kai, Hiroyuki; Nagamine, Kuniaki; Ogawa, Yudai; Nishizawa, Matsuhiko
Abstract : We report a porous polymer microneedle array with continuous micropores that has high mechanical strength and water absorption speed. Abstract : A porous polymer microneedle array with an average pore diameter of ∼1 μm was fabricated by photopolymerization of an acrylate monomer in the presence of a porogen within a mold. Porosity measurement and water absorption testing revealed that the pores are interconnected throughout the microneedle, which enabled rapid wetting of the microneedle by capillary action. The porosity of the polymer microneedles can be modulated by varying porogen content, and this allowed balancing fast water absorption speed and sufficient mechanical strength to penetrate a skin. The developed porous polymer microneedle array is a potentially versatile tool for rapid fluid transport from and into a body through the skin.